International fragmentation and relative wages in the UK - Alexander Hijzen; Holger Görg; Robert C. Hine (Institute for the Study of Labor (IZA), 2003)
This paper re-examines the trade-based explanation of increased wage inequality in developed countries by focusing on international outsourcing. It is the first detailed study to address the effects of outsourcing on labour markets in the UK. In a recent paper, Feenstra and Hanson (1996) estimate the effect of international outsourcing on wage inequality in the US. This paper extends the FH approach by using more detailed definitions of outsourcing and skill. The analysis applies to UK manufacturing over the period 1982-1997. Extending the analysis to the 1990s is considered to be crucial as outsourcing is predominantly a phenomenon of the 1990s. The econometric results suggest that technical change, import penetration and outsourcing all play an important role in explaining UK wage inequality. Outsourcing may account for about half of the increase in domestic wage inequality.
Keywords: F14; J31; 330; outsourcing; trade; wages; skill-biased technological change; fragmentation; Lohnstruktur; Einkommensverteilung; Außenhandelsliberalisierung; Outsourcing; Verarbeitendes Gewerbe; Internationale Arbeitsteilung; Großbritannien